Short Communication: Restoration of seagrass Enhalus acoroides using a combination of generative and vegetative techniques - Rohani Ambo-Rappe; Yayu A. La Nafie; Syafiuddin; Steven R. Limbong; Nenni Asriani; Nur Tri Handayani; Eka Lisdayanti (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Ambo-Rappe R, La Nafie YA, Syafiuddin, Limbong SR, Asriani N, Handayani NT, Lisdayanti E. 2019. Short Communication: Restoration of seagrass Enhalus acoroides using a combination of generative and vegetative techniques. Biodiversitas 20: 3358-3363. Seagrass areas have been declining in extent worldwide, with associated loss in seagrass ecosystem functions and services. Seagrass restoration is important to mitigate, halt and reverse such declines and their consequences. Generative propagation has benefits in terms of genetic biodiversity, however, survival of seagrass seedlings has often been poor especially in high energy environments. Terrestrial restoration often uses shade trees to protect vulnerable seedlings. This study aimed to evaluate the feasibility of a similar approach in the marine environment, using adult plants to protect seedlings of the tropical seagrass Enhalus acoroides (L.f.) Royle. Enhalus seeds taken from a donor bed were germinated and grown into seedlings, then planted in a location with high hydrodynamic exposure at three different densities (high, medium, and low). Adult Enhalus transplants were co-planted to provide three levels of protection: fifty (high), ten (medium), and none (no protection). Results showed that high-density seedling co-planting with high protection from adult transplants had significantly (p< 0.05) higher six-month survival rate compared to the other treatments. Our results indicate that, even in high energy environments, co-planting seedlings with adult transplants may combine the advantages of generative and vegetative propagation methods, promoting greater short-term effectiveness in terms of seedlings survival and growth in the restored seagrass meadows.